Spanish version of the Parkinson's Disease Questionnaire-Carer (PDQ-Carer) - Ferrer-Cascales, R; Cabañero-Martínez, M; Sánchez-Sansegundo, M; Congost-Maestre, N; Jenkinson, C (BioMed Central, 2016)
Background: Parkinson’s caregivers are frequently affected by a range of physical and psychological factors affecting to the quality of life (QoL) of patients and caregivers. However, while there are well-validated QoL instruments for patients, few specific measures has been developed for caregivers of patients with PD. This study examined the psychometric properties of the Spanish version of the Parkinson Disease Questionnaire–Carer (PDQCarer) for use in PD caregivers. Methods: The PDQ-Carer and the Short Form-36 Health Survey (SF-36) were completed by sample of 73 caregivers of patients with PD in Spain (71.8 % females; 63.6 ± 12.3 years old). Results: Psychometric analysis confirmed the reliability and validity of the Spanish version of the PDQ-Carer. The internal consistency was found to be satisfactory for the four PDQ-Carer domains: Personal and Social Activities, Depression and Anxiety, Self-care and Stress with Cronbach’s alpha values ranging 0.80 to 0.95. The PDQ-Carer was significantly correlated with the eight SF-36 domains (r = -0.31 to -0.59, p < 0.001) supporting the concurrent validity of the instrument. Conclusions: Overall, these results provide preliminary evidence of the utility of the Spanish version of the PDQ-Carer in non-professionals caregivers